2017
DOI: 10.1016/j.molcel.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Metabolic Oscillations Robustly Gate the Early and Late Cell Cycle

Abstract: Eukaryotic cell division is known to be controlled by the cyclin/cyclin dependent kinase (CDK) machinery. However, eukaryotes have evolved prior to CDKs, and cells can divide in the absence of major cyclin/CDK components. We hypothesized that an autonomous metabolic oscillator provides dynamic triggers for cell-cycle initiation and progression. Using microfluidics, cell-cycle reporters, and single-cell metabolite measurements, we found that metabolism of budding yeast is a CDK-independent oscillator that oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
149
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 78 publications
11
149
0
Order By: Relevance
“…The Cdc14 depleted cells, increased in volume faster than the Cdc28 depleted cells, indicating early cell cycle activity and biomass synthesis even when the anaphase promoting complex and the late cell cycle are arrested. Consistently, through monitoring the abundance of histone Hta2, previously shown to correlate with DNA content 45, 46 , we found that Cdc14 cells also continued to replicate their DNA, with an approximate rate of one copy per 100 minutes (Fig. 5D).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The Cdc14 depleted cells, increased in volume faster than the Cdc28 depleted cells, indicating early cell cycle activity and biomass synthesis even when the anaphase promoting complex and the late cell cycle are arrested. Consistently, through monitoring the abundance of histone Hta2, previously shown to correlate with DNA content 45, 46 , we found that Cdc14 cells also continued to replicate their DNA, with an approximate rate of one copy per 100 minutes (Fig. 5D).…”
Section: Resultssupporting
confidence: 85%
“…The YSBN16.Whi5-eGFP.Hta2-mRFP1.OsTIR1w/oGFP.G23ARFPex strain (Table S1) was constructed in the following manner: The coding sequence of the OsTIR1 F-box protein was amplified from the pOsTIRw/oGFP plasmid 46 (primers Seq 4 – Table S2), the Hta2-mRFP1 tagging cassette was amplified from the KOY.TM6*P hxk2-GFP hta2-mRFP1 strain 58 (primers Hta2Lin – Table S2), and the Cdc14-AID tagging cassette was amplified from the pG23ARFPex plasmid 46 (primers pG23ALinRFPex – Table S2). The three amplicons were used to transform YSBN16.Whi5-eGFP yeast cells 46 (Table S1) under the selection of G418, phleomycin and ClonNAT respectively, in three separate genomic integration steps.…”
Section: Methodsmentioning
confidence: 99%
“…In one approach, his group uses fluorescent molecular sensors to quantify metabolites, such as ATP. In a forthcoming paper in Molecular Cell, his group has used time-lapse microscopy to watch levels of ATP and another metabolite, NADH (which is autofluorescent), oscillate as the cells go through the cell cycle 8 . Key technical challenges have already been solved when it comes to single-cell metabolomics, Heinemann says.…”
Section: Making Sense Of the Datamentioning
confidence: 99%
“…This phase occurs during the end of mitosis and entry into quiescence (G0). The synchronicity of the cell cycle and metabolic cycle in budding yeast appears to be the result of a system of coupled oscillators, since the metabolic cycle can continue to oscillate in the absence of cell division [65,66] . Intriguingly, the expression of a number of cell cycle genes continues to oscillate with the metabolic cycle even in those cells that are not undergoing cell division, suggesting that the metabolic cycle can regulate cyclic expression of cell cycle genes independently of cell cycle controls [65] .…”
Section: The Mitochondria Meets the Cell Cyclementioning
confidence: 99%